Discrete-time signal processing - Oppenheim, Alan V., 1937-; Schafer, Ronald W., 1938- (Upper Saddle River [N.J.] : Prentice Hall : imprint of Pearson, 2010)
'The definitive, authoritative text on DSP - ideal for those with an introductory-level knowledge of signals and systems. Written by prominent DSP pioneers, it provides thorough treatment of the fundamental theorems and properties of discrete-time linear systems, filtering, sampling, and discrete-time Fourier Analysis. By focusing on the general and universal concepts in discrete-time signal processing, it remains vital and relevant to the new challenges arising in the field.'--Publisher's description.
Discrete-time signals and systems -- The z-transform -- Sampling of continuous-time signals -- Transform analysis of linear time-invariant systems -- Structures for discrete-time systems -- Filter design techniques -- The discrete Fourier transform -- Computation of the discrete Fourier transform -- Fourier analysis of signals using the discrete Fourier transform -- Parametric signal modeling -- Discrete Hilbert transforms -- Cepstrum analysis and homomorphic deconvolution.
Buku Bacaan Asas Fakulti
Includes bibliographical references (p. 1082-1090) and index.
Keywords: Signal processing -- Mathematics; Discrete-time systems